2000
DOI: 10.1038/labinvest.3780185
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of PA2.26 Antigen in Epidermal Keratinocytes Leads to Destabilization of Adherens Junctions and Malignant Progression

Abstract: SUMMARY: PA2.26 antigen is a small mucin-type transmembrane glycoprotein induced in mouse epidermal keratinocytes during carcinogenesis. It is located at plasma membrane projections, such as microvilli and ruffles, where it interacts with the actin cytoskeleton. Previous studies revealed that ectopic expression of PA2.26 in epidermal MCA3D keratinocytes induces cell surface extensions and increased motility. Here, we show that PA2.26-expressing MCA3D (3D2.26) cell transfectants undergo a phenotypic conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 40 publications
4
50
0
2
Order By: Relevance
“…We found, that in vitro silencing of PDPN expression leads to moderately reduced migration, as shown either in transwell migration assay or wound-healing assay, and caused profoundly reduced invasiveness of TPC1 cells, suggesting a potential role of this gene in the spreading of papillary thyroid carcinoma cells. Our observation agrees with several studies which demonstrated involvement of podoplanin in cell migration and invasiveness during cancer progression, and in the promotion of epithelialmesenchymal transition through down-regulation of epithelial genes and up-regulation of mesenychymal markers [16,55,56]. The strong inhibition of the invasiveness of PDPN-silenced TPC1 cells implies an essential function for podoplanin in papillary cancer cell dissemination.…”
Section: Discussionsupporting
confidence: 82%
“…We found, that in vitro silencing of PDPN expression leads to moderately reduced migration, as shown either in transwell migration assay or wound-healing assay, and caused profoundly reduced invasiveness of TPC1 cells, suggesting a potential role of this gene in the spreading of papillary thyroid carcinoma cells. Our observation agrees with several studies which demonstrated involvement of podoplanin in cell migration and invasiveness during cancer progression, and in the promotion of epithelialmesenchymal transition through down-regulation of epithelial genes and up-regulation of mesenychymal markers [16,55,56]. The strong inhibition of the invasiveness of PDPN-silenced TPC1 cells implies an essential function for podoplanin in papillary cancer cell dissemination.…”
Section: Discussionsupporting
confidence: 82%
“…4d). Since mouse PA2.26 was found to destabilize E-cadherin-mediated cell to cell adhesions when expressed in keratinocytes, 20 sections from PA2.26-positive tumours were also stained with an anti-E-cadherin mAb. We found that E-cadherin expression in the tumours was also very heterogenous, with some areas showing an intense staining and others in which E-cadherin staining was fragmented or virtually absent (Fig.…”
Section: Pa226 Is Expressed In Oral Squamous Cell Carcinomasmentioning
confidence: 99%
“…19 Our previous studies suggested that induction of PA2.26 in mouse epidermal cells and tumours was related to cell migration and malignant progression. 6,20 For this reason, we focused on characterizing the human homologue of mouse PA2.26 and on studying its involvement in human cancer. In our study, we report the molecular characterization of human PA2.26.…”
mentioning
confidence: 99%
“…Activated matrix metalloproteinase and destabilization of adherens junctions of PDPN-expressing cells might also be interpreted as the epidermal remodeling process [9,46]. Further study would be required to determine the role of PDPN in terms of proliferation/migration of epidermal keratinocytes.…”
mentioning
confidence: 99%